Quantifying the gap between equilibrium and optimum under monopolistic competition - Kristian Behrens; Giordano Mion; Yasusada Murata; Jens Suedekum (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2018)
Equilibria and optima generally differ in imperfectly competitive markets. While this is well understood theoretically, it is unclear how large the welfare distortions are in the aggregate economy. Do they matter quantitatively? To answer this question, we develop a multi-sector monopolistic competition model with endogenous firm entry and selection, productivity, and markups. Using French and British data, we quantify the gap between the equilibrium and optimal allocations. In our preferred specification, inefficiencies in the labor allocation and entry between sectors, as well as inefficient selection and output per firm within sectors, generate welfare losses of about 6-10% of gdp.
Keywords: 330